Late antiquity on Elephantine Island, Upper Egypt: Pottery as mirror of Roman Society - Katzjäger, Denise (Rei Cretariae Romanae Fautorum Acta, 2015)
Elephantine Island is located opposite the ancient city Syene (Aswan), on the east bank of the Nile in southern Egypt. Both ancient settlements had fully functional Nile harbours through which trading activities could take place, for example the trade in rose granite, which was obtained in local quarries. Furthermore they served as the base for expeditions to Nubia and as military posts at the first cataract region to secure the border to the south. Since the era of the Pharaohs, Elephantine, with its huge sanctuary of the god Chnum, was one of the most famous religious sites within Egypt. In the 5th century AD, as the temple was dismantled, new housing complexes were built at the former temple site. All of them have differing ground plans and, in addition to private use, some include integrated workshops in the courtyards. Previous studies have shown that many inhabitants on Elephantine Island were craftsmen, working with metal, stone and clay, who sold their products over long distances. It is assumed that the housing complexes were inhabited until the 8th or perhaps 9th century AD. The aim of the project is to define the traditions, customs and transformations of the inhabitants of Elephantine Island during the centuries. The pottery of four selected Late Antique and early Byzantine housing complexes will be analysed in detail.